Water deficit-induced changes on growth parameters and radiation use efficiency of promising durum wheat genotypes - Moayedi , A.A.; Nasrulhaq Boyce, A.; Barakbah , S.S.; Kafi, M. (2011)
The present study was carried out to study the performance of durum and bread wheat genotypes in relation to accumulation of dry matter, growth parameters, photosynthetically active radiation interception and radiation use efficiency under different irrigation regimes. The experiment was laid out in a split plot based on a complete randomized block design. Irrigation regime was considered as the main plots and included four levels. Sub-plots were assigned to four durum-promising lines and a bread wheat cultivar. It was observed that water limitation significantly decreased the accumulation of dry matter, growth parameter values, photosynthetically active radiation interception and radiation use efficiency compared to optimum irrigation in the different growth and developmental stages. Water limitation during the post anthesis period decreased the cumulative dry matter by 16 compared to optimum irrigation at the soft dough and physiological maturity stages. It appears that a severe decline in net assimilation rate (NAR) during the reproductive and grain filling phases was related to the high reduction in leaf area index (LAI) and crop growth rate (CGR) at post-anthesis, which consequently caused a severe reduction in the relative growth rate RGR and total dry matter in the same phase. The negative effect of early season water deficit on decreasing leaf area index and dry matter extended until terminal maturity. The application of water deficit from anthesis onwards until late grain filling resulted in a remarkable decline in the photosynthetically active radiation interception at the soft dough and physiological maturity stages. From anthesis to grain filling, the results showed that G2 durum wheat genotype (RASCON3/BEJAH7) and Chamran bread wheat cultivar exhibited the highest values for the photosynthetically active radiation interception. However, the radiation use efficiency was stabilized under water deficit condition due to a simultaneous reduction in the photosynthetically active radiation interception and dry matter accumulation.